E-commerce service quality on customer satisfaction, belief and loyalty: A proposal - Mutia Sobihah, Abd Halim; Nor Azman, Mat Ali @ Salim; Mahadzirah, Mohamad (Mediterranean Centre of Social and Educational Research, 2015)
E-commerce system websites have helped to grow the business into the international field. In the long term in view, it is very important for a business to manage satisfaction, belief, and customer loyalty in the adoption of E-commerce services for business development. In the hotel industry in Malaysia, there is lack of studies on the quality of E-commerce services and has prompted this study to be done. Examine the perception of foreign tourists to the service factors of E-commerce website that influence satisfaction, belief and loyalty are the main objective of this study. Adopting from the previous studies, a conceptual framework of the relationship between E-commerce service quality with satisfaction, belief, and customer loyalty in the hotel industry in Malaysia is established to adapt with this study. The tourism sector is the seventh major provider to the Malaysian economy, with a Gross National Income (GNI) of RM47.2 billion in the year 2013, and is the second leading foreign exchange recipient after manufacture goods. One of the tourism sectors is the hotel industries that have international dimensions and the use of the highest sites. Tourism and hotel industry in particular is a key-driver for economic growth because the industry has proven that it is a catalyst for development.